Revisiting human responsibilities: prospects and challenges - Smith, Liesl Ann Lynn (Department of Political Studies, 2015)
Since the drafting of the Universal Declaration of Human Rights (UDHR) (1948), the extent to which individuals should bear responsibilities for the fulfilment of universal human rights has been a contentiously debated subject. Despite conflicting value-based claims, the approach of international human rights law traditionally has been to recognise states as primary obligation bearers. While the UDHR focuses primarily on state obligations, deliberately unspecified duties of individuals are included under Article 29(1). The meaning of these duties has remained contested, often by relativist critics claiming that a stronger focus on responsibilities would provide a more balanced approach to human rights. The end of the Cold War brought a renewed interest in the normative potential of human rights and a parallel renewal of relativist objections to the universality of the UDHR. In this context transnational campaigns have emerged to advocate for a universal declaration of human responsibilities complementary to the UDHR. The issue has received attention from a number of initiatives, including those of United Nations bodies and agencies and of nongovernmental organisations. The most prominent of these initiatives have received firm opposition from influential Western state and non-state actors. Approaching the topic from a constructivist perspective, this dissertation draws on the social movement literature on the international political opportunity structure to argue that the activities of opponents to human responsibilities initiatives, particularly their framing of human responsibilities as having the potential to undermine and weaken the international human rights framework, have constrained the political opportunities available to human responsibilities campaigns.